Empowering communities for sustainable organic waste management: A composter-based approach - Ramadhani, Farah Salsabila; Maydida, Tiara Dzaky; Widiatmoko, Julian Anindito; Setiyaningsih, Hana; Astri, Anisa Muktidena Mutiara; Marshanda, Angela Rike; Wulandari, Sania; Hasanah, Uswatun; Anggraeni, Aura Kharisma Anggun; Andrian, Budi Wahyu; Achyana, Muchammad Arfan; Mahardhika, Welly; Mardiyah, Siti; Purba, Anirawilda (Universitas Muhammadiyah Magelang, 2025)
Poorly managed organic waste often accumulates, becoming a significant source of pollution. A major challenge is the low utilization rate of waste management facilities. This ongoing issue of organic waste has negative impacts on both public health and quality of life. This initiative aimed to enhance community awareness of waste management and provide guidance on creating composter tools as a solution for organic waste management. The methods employed included waste management sensitization focusing on waste segregation, alongside training on composter construction and usage. Evaluation results indicate that 93% of participants understood the importance of waste segregation, and 93% were able to construct a simple composter after the activity. This program can serve as a sustainable model for waste management, particularly organic waste, at the hamlet level.